2006
DOI: 10.1007/bf02744600
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracic surgery lobectomy reduces the morbidity after surgery for stage I non-small cell lung cancer

Abstract: We conclude that video-assisted thoracic surgery lobectomy for stage I non-small cell lung cancer patients is a less invasive and safer procedure with a lower morbidity rate compared with lobectomy by thoracotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…Several studies reported that VATS resulted in superior rates of postoperative morbidity when compared to thoracotomy. VATS reduced intraoperative blood loss (16,17,(28)(29)(30)(31)(32)(33), chest drain duration and length of hospital stay (28,30,32,34,35). Also, this meta-analysis suggested that the incidence of complications after VATS was less than that in the open lobectomy group, which obviously embodied the micro-invasive characterization of VATS.…”
Section: Discussionmentioning
confidence: 70%
“…Several studies reported that VATS resulted in superior rates of postoperative morbidity when compared to thoracotomy. VATS reduced intraoperative blood loss (16,17,(28)(29)(30)(31)(32)(33), chest drain duration and length of hospital stay (28,30,32,34,35). Also, this meta-analysis suggested that the incidence of complications after VATS was less than that in the open lobectomy group, which obviously embodied the micro-invasive characterization of VATS.…”
Section: Discussionmentioning
confidence: 70%
“…Further, the less time in bed after VATS treatment Non-small-cell Lung Cancer made the patient vigorously coughing and spitting which decrease the complication occurrence of lung infection and atelectasis. However, some reports indicated the reduced complication is only present within two weeks after surgery, and this superiority would weaken after two weeks (Muraoka et al, 2006). Importantly, major trauma could lead to serious acute phase response which may damage the organism immune system and cause decreased anti-tumor ability.…”
Section: Discussionmentioning
confidence: 99%
“…Although only a few reports from Japan were included, recent results after 2005 are shown in Table 2. [20][21][22][23][24][25] Similarly, the blood loss, duration of drainage period, length of hospital stay, and complication rates of VATS were favorable, although the operative time was long. In addition, the postoperative pain level and QOL were also favorable, and favorable outcomes, such as an early return to normal life and conservation of the respiratory function, were achieved.…”
Section: Thoracoscopic Lobectomy For Primary Lung Cancermentioning
confidence: 93%